Family Ownership, Workplace Closure and the Recession - Alex Bryson; Harald Dale-Olsen; Trygve Gulbrandsen (Institute for the Study of Labor (IZA), 2016)
Using nationally representative Norwegian data we show family-owned workplaces are less likely to close than observationally similar non-family-owned workplaces. But this changed during the Crisis when the family businesses' closure hazard soared. This hike in 2009 was not related to performance or the observed capital structure. Whereas bad performance has a tendency to kill non-family businesses regardless of the equity level, a need for fresh capital has a tendency to kill family businesses regardless of performance. We conclude that family firms suffered from a lack of credit during the Crisis, something that policy-makers should address before the next economic downturn.
Keywords: G32; G34; J65; 330; family ownership; closure; financial performance; debt; leverage